Motivation for sport participation of differently-abled elite Filipino male swimmers - Ruiz, Marianne Louise V. 1998-; Guinto, Maria Luisa M. (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2019)
Differently-abled individuals have been negatively perceived by society as inferior human beings. However, there has been increasing interest in differently-abled athletes who have discovered sports as their platform of integration into society. This qualitative study aims to examine the motivation of differently-abled elite Filipino athletes for engaging in sports and the facilitators and barriers to their sports participation. One focus group discussion (FGD) was conducted among four differently-based elite male Filipino swimmers, who were recruited through convenience and snowball sampling. All participants competed at the Paralympics or Para Asean Games. Thematic analysis was used to generate themes grounded in self-determination theory. Results showed five overarching themes that explained the motivation, facilitators and barriers experienced by the athletes: (1) athletes' physical and mental motivations (2) the crucial role of social networks (3) opportunities leading to sports involvement (4) change in the outlook of life and (5) negotiating barriers. These themes indicated that, although athletes were motivated by both internal and external factors, they gave greater emphasis to their intrinsic motivation to engage in sports. Results also showed that internal satisfaction, empowerment, external rewards, social support, recruitment and being with fellow differently-abled athletes facilitated their sports participation; while discrimination, poor time management, lack of financial support, and limited sporting facilities served as barriers to their sports participation.
Vita.
Thesis (Bachelor in Sports Science)--University of the Philippines Diliman
Keywords: Motivation (Psychology).; Swimming for people with disabilities -- Philippines; Sports -- Psychological aspects..